Oral Trypanosoma cruzi Acute Infection in Mice Targets Primary Lymphoid Organs and Triggers Extramedullary Hematopoiesis - Marins-Dos-Santos, Alessandro; Ayres-Silva, Jackline de Paula; Antunes, Dina; Moreira, Carlos José de Carvalho; Pelajo-Machado, Marcelo; Alfaro, David; Zapata, Agustín G.; Bonomo, Adriana Cesar; Savino, Wilson; de Meis, Juliana; Farias-de-Oliveira, Désio Aurélio (Frontiers in Cellular and Infection Microbiology, 2022)
During the acute phase of Chagas disease, Trypanosoma cruzi circulation through the blood stream leads to high tissue parasitism in the host. In primary lymphoid organs, progenitor cell reduction paralleled transient immunosuppression. Herein we showed that acute oral infection in mice promotes diffuse parasitism in the bone marrow cells at 14- and 21-days post-infection (dpi), with perivascular, intravascular and regions near the bone being target sites of parasite replication. Phenotypic analysis of hematopoietic differentiation in the bone marrow of infected mice showed that cell number in the tissue is decreased in the acute phase (Lineage negative and positive cells). Interestingly, analysis of hematopoietic branch point in lineage negative cells showed that Hematopoietic stem and progenitor cells (HSPCs) were significantly increased at 14 dpi. In addition, hematopoietic stem cells (HSCs) at 14 and 21 dpi, and multipotent progenitors (MPPs) also showed this pattern of increase at 14 dpi. In contrast, subsequent progenitors give rise up from MPPs, such as common lymphoid progenitors (CLPs) and myeloid progenitors were not enhanced, conversely, both present numeric decline 21 and 14 dpi. Annexin V staining revealed that CLPs and CMPs decrease at 14 and 21 dpi at the bone marrow of infected mice is not linked to cell death. Finally, these results led us to investigate HSPCs presence in the spleen such as the phenomenon triggered during hematopoietic emergencies due to mobilization or expansion of these cells in extramedullary sites. In this sense, splenocyte analysis showed a progressive increase in HSPCs cells between 14 and 21 dpi. Altogether, our study shows that bone marrow is a target tissue in orally T. cruzi infected mice, leading to hematopoietic disturbance and consequent myeloid progenitors and CLPs reduction, together with a defective thymocyte development and extramedullary hematopoiesis, as seen in the spleen.